Obesity of children and adults - pandemic of the 21st century - Panasiuk, Dominika; Szponarowicz, Patrycja; Panek, Eliasz; Jasłowski, Damian; Rzeszutko, Mateusz; Raczkiewicz, Przemysław; Skrętowicz, Mateusz; Snopkowski, Bartosz; Korzec, Tomasz; Sosnowski, Jakub (Journal of Education, Health and Sport, 2023)
Objective: The aim of the study was to draw attention to the problem of overweight and obesity among children and adults. Another important aspect of this article was to indicate the need of promotion a healthy lifestyle as a way to reduce body weight. Methods: Available literature was reviewed for the purpose of writing this article. Using keywords such as obesity, overweight, pandemics, diet, lifestyle, chronic diseases, metabolic disorders- PubMed was searched. Results: The incidence of overweight and obesity is constantly increasing. This phenomenon is observed all over the world. Obesity has become a pandemic of the 21st century. Consumption of unhealthy, highly processed food is increasing these days. In addition, sedentary lifestyle is very popular. Lifestyle and diet changes are the main causes of this pandemic. The SARS-CoV-2 virus also had an impact on the development of the obesity and overweight pandemic. Obesity affects the quality of life and causes many chronic diseases. The effects on the community are also significant. Obesity and related diseases like diabetes, ischemic heart disease, heart attacks, asthma result in high health care costs. Conclusion: The percentage of overweight and obese people around the world is increasing. It is necessary to promote healthy eating, active lifestyle and look for alternative ways to reduce the scale of overweight and obesity problem.